Aesthetics of Production and Aesthetics of Reception in Analyzing Intertextuality: Illustrated with Joshua 2 - Krause, Joachim J. (Biblica, 2015)
That intertextuality has come into vogue in Hebrew Bible scholarship is hardly surprising given some general trends in the field. In fact, the reconstruction of redactional activity and 'Fortschreibung' as well as inner-biblical interpretation are heavily dependent on the perception of intertextual relationships. But therein lies the problem. Has the perceived relationship indeed been established by the author of one of the biblical texts in question (aesthetics of production), or does it merely lie in the eye of the beholder (aesthetics of reception)? Two competing claims regarding an intertextual relationship of Joshua 2 are singled out for discussion.